Hello iDrum Originally Posted by

**iDrum** ...

*Solve each equation for x:*

48.) (2x-3)(2x-3) = 4

Write this as: $\displaystyle (2x-3)^2=4$

and then take square roots, not forgetting the $\displaystyle \pm$ sign on the right:$\displaystyle 2x-3=\pm2$

$\displaystyle \Rightarrow 2x = 3+2$ or $\displaystyle 3-2$

$\displaystyle \Rightarrow x = 2.5$ or $\displaystyle 0.5$

52.) a.) 12x^2 - 5x -3 = 0

$\displaystyle 12x^2 - 5x -3 = 0$

$\displaystyle \Rightarrow(3x+1)(4x-3)=0$

Can you complete it?

This won't factorise, so use the formula: $\displaystyle x=\frac{-13\pm\sqrt{13^2-4(30)(-10)}}{60}$

Can you complete it?

Grandad